Method for additive manufacturing of La (Fe, Si) 13-based magnetic refrigeration material with high compressive mechanical strength
Through additive manufacturing technology, the La(Fe,Si)13 series magnetic refrigeration functional material with high compression mechanical strength was prepared, which solved the problem of insufficient mechanical properties of the materials in the prior art, achieved the combination of high strength and high magnetic entropy change, and improved the application potential of the materials.
Patent Information
- Application Number
- CN202410806219.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the mechanical properties of La(Fe,Si)13 series alloys are insufficient, and there are cracks and brittle problems during the preparation process, which limits their application in practical applications.
Administrative manufacturing method, La(Fe,Si)13-type magnetic refrigeration functional materials with high compression mechanical strength are prepared through technologies such as selective laser melting or electron beam melting. The specific steps include configuring alloy components rich in rare earth elements, performing vacuum induction smelting, preparing spherical powders, and depositing bulk materials through additive manufacturing, followed by heat treatment and water quenching.
The high compression mechanical strength of the La(Fe,Si)13 series magnetic refrigeration functional material is realized, with a compression strength of more than 570MPa, while maintaining a high magnetic entropy change, solving the brittleness and crack problems of the material, and improving its application potential in magnetic refrigeration technology.
Smart Images

Figure CN119588954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic refrigeration, and in particular relates to a novel high-strength magnetic refrigeration functional material and a preparation method and application thereof. Background Art
[0002] Refrigeration is an extremely important technology that is widely used in various industries, from small civilian refrigerators and air conditioners to the storage of plasma vaccines in the biological field, and large military and aerospace detectors. All of these fields cannot do without the support of refrigeration technology. At present, the main method of industrial refrigeration is gas compression refrigeration based on working fluids such as Freon and carbon dioxide. It has low energy efficiency, high noise, and is not environmentally friendly. With the signing of the Montreal Protocol, countries have regulated and restricted the emission of chlorofluorocarbons, so it is particularly urgent to find a new environmentally friendly refrigeration method to replace traditional refrigeration.
[0003] As a new type of solid-state refrigeration technology, magnetic refrigeration technology is expected to become a new technology to replace gas compression refrigeration with its advantages of being pollution-free, highly efficient and energy-saving.
[0004] Among the many magnetic refrigeration fluids available, La(Fe,Si) 13 La(Fe,Si) based alloy has the characteristics of large magnetocaloric effect, non-toxicity and easy adjustment of Curie temperature, and is one of the most promising materials at present. 13 The magnetocaloric effect of the base alloy is attributed to NaZn 13 This type of metastable phase requires high-temperature heat treatment to promote the peritectic reaction between α-(Fe,Si) and La1Fe1Si1 phases, and then rapid quenching to obtain it.
[0005] As the Si content increases, La(Fe,Si) 13 The Curie temperature of the alloy increases from 198K to 262K. However, when the Si content exceeds 1.6at.%, it has a negative impact on the magnetocaloric properties. Partial substitution of La by Gd can improve the LaFe 11.4 Si 1.6 The Curie temperature of La(Fe,Si) can be increased by 1.5 % and 2.5 % respectively, which broadens its isothermal magnetic entropy change peak, but is harmful to the magnetocaloric effect. 13 Magnetocaloric effect of alloys. Co, Cu, Ni, Cr and some interstitial atoms (B, C, H) are effective in reducing the hysteresis inherent in the first-order phase transition, but inevitably reduce the magnetocaloric effect.
[0006] In addition, La(Fe,Si) 13The alloy exhibits a typical first-order magnetic phase transition, which is accompanied by a strong magnetic volume effect. The volume change during the magnetization and demagnetization cycle in service will lead to the initiation and expansion of cracks. In addition, the intrinsic brittleness of the system and poor mechanical properties have become the biggest obstacles to its practical application. Therefore, finding a suitable method to prepare high-strength La-Fe-Si materials is a prerequisite for its commercialization.
[0007] CN106381133A discloses a La-Fe-based magnetic refrigeration composite material. The La-Fe-based magnetic refrigeration material with good phase formation is mechanically ground and screened to obtain a coarse main phase powder of 180-250μm and a fine main phase powder of less than 45μm. The two powders are mixed in proportion, and then 9-11% of metal tin powder is added and mixed evenly, and then hot-pressed to obtain a La-Fe-based magnetic refrigeration composite material. The material has high density, high strength and high magnetocaloric properties.
[0008] CN102516950A discloses a working component for magnetic heat exchange and a method for manufacturing a working component for magnetic refrigeration, wherein the working component for magnetic heat exchange includes a magnetocalorically active phase, wherein the magnetocalorically active phase includes La1-aRa(Fe1-x-yTyMx)13Hz, the hydrogen content z is 90% or more of the hydrogen saturation value, the values of a, x and y are to give the Curie temperature Tc, M is one or more of Al and Si, T is one or more of Co, Ni, Mn, Cu, Ti, V, and R is one or more of Ce, Nd, Y, Pr. Summary of the invention
[0009] The present invention aims to overcome the existing technology for preparing La(Fe,Si) 13 The disadvantage of insufficient mechanical properties of the series alloys is that a method is provided to prepare a new type of high-temperature magnetic refrigeration functional material with high compressive mechanical strength through additive manufacturing.
[0010] A method for preparing a magnetic refrigeration functional material with high compressive mechanical strength comprises the following steps:
[0011] (1) Preparing raw materials according to alloy composition rich in rare earth elements;
[0012] (2) melting the raw materials and preparing alloy bars;
[0013] (3) Cut off the bar riser and then use mechanical processing to remove the oxide layer on the surface of the bar;
[0014] (4) Using alloy rods as raw materials, spherical powders are prepared by gas atomization or rotating electrode method;
[0015] (5) using additive manufacturing methods, including but not limited to selective laser melting to deposit bulk materials;
[0016] (6) The parts are separated from the printed substrate, and after removing the surface oxide layer, they are heat treated in an inert gas atmosphere and water quenched.
[0017] The alloy composition in step (1) is (La a Ce 1-a ) x (Fe b Co 1-b ) y Si 13-y , where a, b, x, and y are atomic percentages, and 0.4≤a≤1.0, 0.5≤b≤1.0, 1.0 <x≤2.0,11.0≤y≤12.0。
[0018] The smelting method in step (2) is vacuum induction melting or directional solidification. The vacuum degree of the furnace chamber during the smelting process is 1-100 Pa, more preferably 5-10 Pa. After impurity removal treatment, the oxygen content in the furnace is less than 5 ppm, more preferably less than 2 ppm, and the content of other heteroatoms is less than 100 ppm, more preferably less than 20 ppm.
[0019] In step (4), spherical powder particles are prepared, and the average particle size of the particles is less than 100 μm, more preferably 50-90 μm.
[0020] The additive manufacturing method in step (5) is one of selective laser melting (SLM), selective laser sintering (SLS), and electron beam melting (EBM); preferably, it is laser melting (SLM) or electron beam melting (EBM).
[0021] The selective laser melting (SLM) manufacturing method constructs a 90° rotation of the laser direction between adjacent deposited layers; the laser power is 100-200W, and the scanning speed is 300-600mm·s -1 , the printing distance is 50-150μm, the laser diameter is 30-80μm, and the interlayer thickness is 20-50μm.
[0022] The electron beam melting (EBM) manufacturing method has an electron beam melting current of 5-20 mA, a focus compensation of 0.1-0.5 mA, a beam spot moving speed of 300-600 mm / s, and an interlayer thickness of 20-80 μm. The entire process needs to be carried out within 0.5-5×10 -3 mBar vacuum.
[0023] The heat treatment process in step (6) is to seal the sample into a quartz tube. Before sealing the tube, the quartz tube needs to be evacuated to a high vacuum and filled with high-purity argon as a protective gas.
[0024] The heat treatment time in step (6) is 5 min to 120 h, the heat treatment temperature is 1073 to 1673 K, and water quenching is used after the heat treatment is completed, more preferably 30 min to 24 h, and the heat treatment temperature is 1300-1400 K.
[0025] Another aspect of the present invention discloses a novel high-temperature magnetic refrigeration functional material with high compressive mechanical strength prepared by the method of the present invention.
[0026] The compressive strength of the magnetic refrigeration functional material is greater than 550 MPa, and more preferably greater than 570 MPa; the maximum magnetic entropy change of the magnetic refrigeration functional material at 283K is greater than 7.0 J / (Kg·K), and more preferably greater than 7.5 J / (Kg·K).
[0027] The crystal structure and phase identification of the samples were performed using an Empyrean X-ray diffractometer from Malvern Panalytical. The microstructure of the samples was observed using a scanning electron microscope (SEM) in backscattered electron (BSE) mode. The magnetic properties of the samples were measured using PPMS, and the magnetic entropy change value of the material was obtained by solving the Maxwell equations of the isothermal magnetization curve tested. The samples were mechanically compressed using an MTS CMT-5202 universal material testing machine to obtain the mechanical properties.
[0028] Experiments have shown that the (La a Ce 1-a ) x (Fe b Co 1-b ) y Si 13-y High-temperature magnetic refrigeration functional materials, after annealing, the cracks produced by 3D printing self-heal, the alloy has high compressive strength, and also has a considerable magnetic entropy change, which can be applied to magnetic refrigeration technology.
[0029] Beneficial technical effects of the present invention: The magnetic refrigeration material workpiece obtained by the present invention has a high magnetic entropy change, significantly improved mechanical properties, especially compressive strength, and good formability of the workpiece, and can be used to process workpieces of various complex configurations, thereby reducing production costs and improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the pre-alloyed gas atomized powder in the present invention;
[0031] Figure 2 a is a diagram of the deposition strategy of 3D-printed alloys;
[0032] Figure 2 b is the appearance of the 3D printed alloy;
[0033] Figure 3 a is the XRD pattern of the 3D printed sample before annealing in the embodiment;
[0034] Figure 3 b is the XRD pattern of the 3D printed sample after annealing in the embodiment;
[0035] Figure 4 a is the SEM image of the 3D printed sample before annealing in the embodiment;
[0036] Figure 4 b is a SEM image of the crack healing of the 3D printed sample after annealing in the embodiment;
[0037] Figure 5 The stress-strain curve of the 3D printed sample after annealing in the embodiment;
[0038] Figure 6 It is the magnetic entropy change curve of the 3D printed sample after annealing in the embodiment; DETAILED DESCRIPTION
[0039] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0040] Example 1
[0041] The selective laser melting method was used to prepare 0.6 Ce 0.4 ) 1.49 (Fe 0.91 Co 0.09 ) 11.46 Si 1.54 Magnetic refrigeration functional materials, first of all, according to the composition ratio, the raw materials with a purity of more than 99.9% are prepared, and alloying treatment is carried out by induction melting to obtain the required original master alloy. After removing the surface and riser of the master alloy rod by cutting and grinding, atomization powder is carried out to obtain spherical powder. Spherical powder with a particle size of 15 to 53 microns is selected as the raw material, and the bulk alloy is prepared by selective laser melting (SLM). Printing strategy such as Figure 2 As shown in a, the laser direction is rotated 90° between adjacent deposition layers (n layer and n+1 layer). The laser power is 150W and the scanning speed is 500mm·s -1 , the printing distance is 90μm, the laser diameter is 60μm, and the interlayer thickness is 30μm. Figure 3 a shows the XRD spectrum of the additively manufactured bulk alloy. The main phases of the printed sample are α-Fe phase and La1Fe1Si1 phase. The printed bulk alloy was sanded to remove the surface oxide layer, sealed in a quartz tube with an argon atmosphere, and annealed at 1323K for 30 minutes. After the heat treatment, it was quenched in water. The annealed sample was tested by XRD, and the results are shown in Figure 1. Figure 3As shown in b, after annealing, there is a large amount of NaZn 13 type phase is generated, and a small amount of α-Fe remains.
[0042] Figure 4 a and Figure 4 b are SEM images of the printed alloy before and after heat treatment. It can be seen from the figure that before heat treatment, there are a large number of cracks on the surface of the printed sample. After heat treatment, the cracks heal and disappear. Figure 5 This is the stress-strain curve of the 3D printed sample after annealing. It can be concluded from the figure that the fracture form of the sample after heat treatment is brittle fracture, and its compressive strength reaches 570MPa.
[0043] Figure 6 This is the magnetic entropy change curve of the sample after annealing. At 283K, the sample has a maximum magnetic entropy change of 7.5J / (Kg·K).
[0044] Example 2
[0045] In this embodiment, La is prepared by selective laser melting. 1.5 Fe 11.6 Si 1.4 Magnetic refrigeration functional materials, first of all, prepare raw materials with a purity of more than 99.9% according to the composition ratio, place the raw materials in a vacuum induction furnace for smelting, and pour them into a water-cooled copper mold to obtain a rod-shaped sample. Use cutting and grinding to remove the surface of the master alloy rod, and cut off the riser. Then use the rotating electrode method to atomize and pulverize to obtain spherical powder. Spherical powder with a particle size of 15 to 53 microns is selected as the raw material, and the microchannel block is prepared by selective laser melting (SLM), and the channel diameter is ~1mm. The laser power is 140W and the scanning speed is 600mm·s -1 , the lap spacing is 90μm, the laser diameter is 60μm, and the interlayer thickness is 20μm. The microfluidic block and the substrate are separated by wire cutting, and the surface oxide layer is polished off with sandpaper, then sealed in a quartz tube with an argon atmosphere, and heat treated at 1323K for 12h and water quenched.
[0046] Example 3
[0047] In this embodiment, electron beam melting method is used to prepare (La 0.7 Ce 0.3 ) 1.8 (Fe 0.91 Co 0.09 ) 11.5 Si 1.5Magnetic refrigeration functional materials, first of all, prepare raw materials with a purity of more than 99.9% according to the composition ratio, and then use a directional solidification furnace to prepare rods. Use cutting and grinding to remove the surface of the master alloy rod, and cut off the riser. Then use the rotating electrode method to gas atomize and pulverize to obtain spherical powder. Spherical powder with a particle size of ~40 microns is selected as the raw material, and cubic blocks are prepared by electron beam melting. The electron beam melting current is 10mA, the focus compensation is 0.25mA, the beam spot moving speed is 500mm / s, the interlayer thickness is 50μm, and the whole process needs to be 2×10 -3 After the deposition is completed, the microchannel block and the substrate are separated by wire cutting, and the oxide layer on the surface is polished off with sandpaper, and then sealed in a quartz tube with an argon atmosphere, and heat treated at 1323K for 12h and water quenched.
[0048] Comparative Example 1
[0049] Yanyan Shao et al. prepared La-Fe-Si / Fe magnetocaloric composites by hot pressing in their paper entitled Impact of interface structure on functionality in hot-pressed La-Fe-Si / Fe magnetocaloric composites (Shao Y, Liu Y, Wang K, et al. Impact of interface structure on functionality in hot-pressed La-Fe-Si / Fe magnetocaloric composites, Acta Materialia, 2020, 195, 163-171; DOI: https: / / doi.org / 10.1016 / j.actamat.2020.04.042). 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 / 13.5%Fe composite material. A mechanical compression test was carried out on the hot-pressed magnetic refrigeration material using a universal testing machine, and the results showed that the maximum strength of the material was 300MPa.
[0050] Comparative Example 2
[0051] Abd El-Moez A.Mohamed et al. published a paper entitled Enabling high efficiency magnetic refrigeration using laser powder bed fusion of porous LaCe(Fe,Mn,Si)13 structures paper (Abd El-Moez A.Mohamed,Minki Jeong,Richard S.Sheridan,etal.Enabling high efficiency magnetic refrigeration using laser powder bedfusion of porous LaCe(Fe,Mn,Si) 13 structures, Additive Manufacturing, 2022, 51, 102620; DOI: https: / / doi.org / 10.1016 / j.addma.2022.102620), LaCe(Fe, Mn, Si) was prepared by LPBF method (3D printing) 13 The maximum compressive mechanical stress value of the alloy is 90MPa.
[0052] Comparative Example 3
[0053] Yue-qiao Li et al. published a paper entitled Excellent mechanical properties and agestability of hydrogenated La 0.8 Ce 0.2 Fe 12.5 Mn 0.2 Si 1.3 H δ plates with extra Fe in the paper (Yue-qiao Li, Feng-xia Hu, Fei-ran Shen, etal.Excellent mechanical properties and age stability of hydrogenated La 0.8 Ce 0.2 Fe 12.5 Mn 0.2 Si 1.3 H δ plates with extra Fe, Journal of Alloys and Compounds, 2018, 743, 221-226; DOI: https: / / doi.org / 10.1016 / j.jallcom.2018.01.381), La plates with extra Fe were prepared directly by conventional arc melting technology. 0.8 Ce 0.2 Fe 12.5 Mn0.2 Si 1.3 The ingots were cut into sheets with a thickness of about 0.4-0.6 mm and annealed at 1323 K. The compressive strength test was performed by compressing four overlapping sheets at ambient temperature using a universal material testing machine, and the compressive strength could reach 352 MPa.
[0054] Comparative Example 4
[0055] Oleksandr Glushko et al. reported in their paper entitled Mechanical properties of the magnetically intermetallic LaFe 11.2 Si 1.8 alloy at different length scales in the paper (Oleksandr Glushko, Alexander Funk, Verena Maier-Kiener, et al. Mechanical properties of the magnetocaloric intermetallic LaFe 11.2 Si 1.8 alloy at different length scales, Acta Materialia, 2019, 165, 40-50; DOI: https: / / doi.org / 10.1016 / j.actamat.2018.11.038), LaFe was prepared by arc melting 11.2 Si 1.8 The compressive strength of the alloy sample with an aspect ratio of 2.5:1 is 403 MPa.
[0056] Comparative Example 5
[0057] The La was prepared by the metal powder hot pressing method in the prior art. 0.8 Ce 0.2 (Fe 0.95 Co 0.05 ) 11.8 Si 1.2 / Sn magnetic refrigeration material: mechanically grind the well-formed La-Fe-based magnetic refrigeration material and screen out the coarse main phase particles of 180-250μm and the fine main phase powder less than 45μm; mix the two particle sizes of La-Fe-based magnetic refrigeration materials in different weight ratios, then add 9% to 11% of metal tin powder according to the total weight and mix them evenly; hot molding and forming, the processing parameters are: heat the mold to 140-155℃, then pressurize to 900-1000MPa, keep the temperature and pressure for 1-3 minutes and then stop heating. La prepared by the above method0.8 Ce 0.2 (Fe 0.95 Co 0.05 ) 11.8 Si 1.2 The maximum compressive strength of the / Sn compound is 224.8MPa.
[0058] Comparative Example 6
[0059] Preparation (La 0.6 Ce 0.4 ) 1.49 (Fe 0.91 Co 0.09 ) 11.46 Si 1.54 Magnetic refrigeration functional materials, firstly, raw materials with a purity of more than 99.9% are prepared according to the composition ratio, and alloyed by induction melting to obtain the required original master alloy. The surface and riser of the master alloy rod are removed by cutting and grinding, and then atomized powder is made to obtain spherical powder. Spherical powder with a particle size of 15 to 53 microns is selected as the raw material, and is evenly mixed with a low melting point metal or alloy to form a mixed powder; the mixed powder is placed under a pressure of 8×10 -2 Pa or in an inert atmosphere, the pressing pressure is 500MPa, the hot pressing temperature is 200℃, and the holding time is 10min. 0.6 Ce 0.4 ) 1.49 (Fe 0.91 Co 0.09 ) 11.46 Si 1.54 The maximum compressive strength of the alloy is 483MPa.
[0060] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the present invention, they shall all fall within the protection scope of the present invention.
Claims
1. An additive manufacturing method for high compressive strength La(Fe,Si) 13 The method of the base magnetic refrigeration material comprises the following steps: (1) Preparing raw materials according to alloy composition rich in rare earth elements; (2) melting the raw materials and preparing alloy bars; (3) Cut off the bar riser and then use machining to remove the bar surface; (4) Using alloy rods as raw materials, spherical powders are prepared by gas atomization or rotating electrode method; (5) using additive manufacturing methods, including but not limited to selective laser melting to deposit bulk materials; (6) The parts are separated from the printed substrate, and after removing the surface oxide layer, they are heat treated in an inert gas atmosphere and water quenched.
2. The method according to claim 1, characterized in that The alloy composition in step (1) is (La a Ce 1-a ) x (Fe b Co 1-b ) y Si 13-y , where a, b, x, and y are atomic percentages, and 0.4≤a≤1.0, 0.5≤b≤1.0, 1.0 <x≤2.0,11.0≤y≤12.0。 3. The method according to claim 1, characterized in that The smelting method in step (2) is vacuum induction melting or directional solidification. The vacuum degree of the furnace chamber during the smelting process is 1 to 100 Pa, more preferably 5 to 10 Pa. After impurity removal treatment, the oxygen content in the furnace is less than 5 ppm, more preferably less than 2 ppm, and the content of other heteroatoms is less than 100 ppm, more preferably less than 20 ppm.
4. The method according to claim 1, characterized in that The average particle size of the spherical particles prepared in step (4) is less than 100 μm, more preferably 50-90 μm.
5. The method according to claim 1, characterized in that In step (5), the additive manufacturing method is one of selective laser melting (SLM), selective laser sintering (SLS), and electron beam melting (EBM), preferably laser melting (SLM) or electron beam melting (EBM).
6. The method according to claim 5, characterized in that The selective laser melting (SLM) manufacturing method constructs a 90° rotation of the laser direction between adjacent deposited layers; the laser power is 100-200W, and the scanning speed is 300-600mm·s -1 , printing distance is 50-150μm, laser diameter is 30-80μm, and interlayer thickness is 20-50μm; The electron beam melting (EBM) manufacturing method has an electron beam melting current of 5-20 mA, a focus compensation of 0.1-0.5 mA, a beam spot moving speed of 300-600 mm / s, and an interlayer thickness of 20-80 μm. The entire process needs to be carried out within 0.5-5×10 -3 mBar vacuum.
7. The method according to claim 1, characterized in that The heat treatment process in step (6) is to seal the sample into a quartz tube. Before sealing the tube, the quartz tube needs to be evacuated to a high vacuum and filled with high-purity argon as a protective gas.
8. The method according to claim 1, characterized in that The heat treatment time in step (6) is 5 minutes to 120 hours, the heat treatment temperature is 1073 to 1673K, and water quenching is used after the heat treatment is completed.
9. A novel high-temperature magnetic refrigeration functional material with high compressive mechanical strength prepared according to the method of any one of claims 1 to 8.
10. The novel high-temperature magnetic refrigeration functional material according to claim 9, characterized in that The compressive strength of the magnetic refrigeration functional material is greater than 550MPa, and more preferably greater than 570MPa; the maximum magnetic entropy change of the magnetic refrigeration functional material at 283K is greater than 7.0J / (Kg·K), and more preferably greater than 7.5J / (Kg·K).
Citation Information
Patent Citations
Working component for magnetic heat exchange and method of producing a working component for magnetic refrigeration
CN102516950A
La-Fe based magnetic refrigeration composite material and preparation method thereof
CN106381133A